PERSEPSI MAHASISWA TERHADAP IKLAN SMARTPHONE PRODUK OPPO RENO2 SERIES STORYGRAPHER PADA MAHASISWA ILMU KOMUNIKASI UNIVERSITAS DWIJENDRA - Gede Bagus, Anak Agung; Ayu Nareswari, Putu (Jurnal Kajian Ilmu Komunikasi, 2021)
The purpose of this study is to find out how the perception of communication science students of Universitas Dwijendra on the creativity of Smartphone Oppo Reno2 Series Storygrapher". Theories considered relevant in this research are Communication, Mass Communication, Communication Technology, New Media, Internet As Media Advertising, Social Media, Advertisement, Creative Advertising Strategy and Perception. This research is quantitative research using quantitative descriptive method. The total population in this study is 82 people, the sample determination using Slovin formula so that the sample obtained as many as 68 people. Sampling technique in this study using Purposive Sampling. Data collection technique in this research is library research and field research. Data analysis technique performed is single table